Polishing and wear behaviour of sintered alumina-silicon carbide nanocomposites - Cock, A; Wu, H; Roberts, S (2001)
Alumina-silicon carbide nanocomposites have been observed to have polishing behaviour superior to that of pure alumina, although detailed studies of this effect are reported sparsely. This paper presents a systematic study of the polishing behaviour, under different conditions, of pressureless sintered nanocomposites made from powders which were prepared under near-industrial conditions. The polished surfaces were characterised by surface roughness measurements combined with reflected light microscopy. The results are compared with those from nanocomposites made from powders prepared under laboratory conditions. For both sets of samples, the polishing behaviour is improved compared to that of alumina. Microscopy clearly shows that the improved behaviour is due primarily to a change from intergranular fracture in alumina to predominantly transgranular fracture in the nanocomposites. This change is connected with the different subsurface deformation mechanisms as observed by transmission electron microscopy of polished nanocomposites.